Isolation and characterization of cellulose degrading ability in Paenibacillus isolates from landfill leachate - Chien, P.; Yoo, H.; Dykes, Gary; Lee, S. (2015)
Aims: Cellulases are enzymes that convert cellulose into glucose molecules, and are produced by various microorganisms in the environment. Due to their importance to the biofuel industry, there is a need to screen for more efficient varieties of cellulases. In this study, leachate samples from a landfill site were screened for cellulolytic bacteria. Methodology and results: Leachate samples obtained from a landfill collection pond were cultured in an enriched cellulose medium. Two cellulolytic isolates, designated MAEPY1 and MAEPY2, were isolated and further characterized. Phenotypic profiles and phylogenetic analyses using sequences of 16S rRNA, gyrB and whole genome suggested that these isolates are new strains of the Paenibacillus genera. The crude enzyme extracts from both isolates have cellulose degradation activity at approximately 0.1-0.2 IU/mg under working conditions of pH 6 and 55 °C. Assays using other lignocellulosic substrates showed that the crude enzyme extracts also have high xylan degradation activity. Conclusion, significance and impact of study: Paenibacillus sp. are known to produce multiple enzymes for lignocellulolytic degradation and the present results suggest that isolates described in this study, MAEPY1 and MAEPY2, are excellent candidates deserving further study as potential producers of efficient cellulases for use in industries associated with cellulosic biomass.